Sexism and Gendered Medical Specialty Preferences among Medical Students at UIN Jakarta - Hasina Putri Maharani (Departemen Sosiologi Universitas Gadjah Mada, 2025)
Anchored in Joan Acker’s theory of gendered organizations, this study examines how institutionalized gender norms influence medical specialty preferences. Gendered perceptions often reinforce occupational segregation, where “masculine” specialties are male-dominated and “feminine” ones by women. This research aims to identify gender differences in specialty preferences and the extent to which stereotypes, segregation, sexism, and patriarchy shape these preferences among 211 medical students at UIN Jakarta. Data were collected via questionnaires and analyzed using T-tests and logistic regression in STATA 13. Results reveal that female students show stronger preferences for Dermatology and Venereology, and Obstetrics and Gynecology, fields typically associated with femininity. Hostile sexism had no significant effect, while benevolent sexism exhibited nuanced influences: beliefs in female purity positively correlated with Internal Medicine, whereas beliefs in female frailty correlated positively with Dermatology and Venereology, and Obstetrics and Gynecology, but negatively with Internal Medicine. Segregation negatively affected Internal Medicine preference, and stereotypes were negatively associated with Dermatology and Venereology, and Cardiovascular. Domestic patriarchal roles increased preference for Surgery but decreased interest in Pediatrics and Psychiatry. While public patriarchal roles had opposite effects, promoting Pediatrics preference while reducing interest in Obstetrics and Gynecology. These findings highlight how entrenched gendered and cultural logics continue to shape medical specialty preferences within institutional contexts.